2017
DOI: 10.1021/acs.jpca.7b05965
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Rates of U(VI) Reduction by Fe(II) in Homogeneous Aqueous Solution and the Role of U(V) Disproportionation

Abstract: Molecular-level pathways in the aqueous redox transformation of uranium by iron remain unclear, despite the importance of this knowledge for predicting uranium transport and distribution in natural and engineered environments. As the relative importance of homogeneous versus heterogeneous pathways is difficult to probe experimentally, here we apply computational molecular simulation to isolate rates of key one electron transfer reactions in the homogeneous pathway. By comparison to experimental observations th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 49 publications
2
21
1
Order By: Relevance
“…The complex 5 was independently prepared from the reaction of UI 4 and 2 equiv of K 2 dpaea and crystallographically characterized (Figure S36). These results indicated that the monomeric uranyl (V) complex undergoes disproportionation upon protonation of the uranyl oxo groups as suggested by previous computational studies …”
supporting
confidence: 82%
“…The complex 5 was independently prepared from the reaction of UI 4 and 2 equiv of K 2 dpaea and crystallographically characterized (Figure S36). These results indicated that the monomeric uranyl (V) complex undergoes disproportionation upon protonation of the uranyl oxo groups as suggested by previous computational studies …”
supporting
confidence: 82%
“…However, uncertainty about its presence and of its role in reduction pathways involving iron oxides remains. The reduction of U(VI) to U(IV) can occur via (a) two single-electron transfer steps, from U(VI) to U(V), and U(V) to U(IV), or (b) from U(VI) to U(V) followed by disproportionation of two U(V) to U(VI) and U(IV) 22 , 27 29 . Theoretical calculations reported the reduction from U(VI) to U(V) by aqueous Fe(II) to be facile 29 and demonstrated that the incorporation of U in solid phases widens the stability field of U(V) species in the reduction by magnetite 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, computational approaches have been employed as important tools to predict several essential properties of actinides relevant to nuclear waste management and safe disposal such as electronic structure and bonding 5 , hydration [6][7][8] , speciation [9][10][11][12] , redox chemistry [13][14][15][16][17][18][19][20] , spectral properties [21][22][23][24] , reaction mechanisms [25][26][27][28][29][30][31][32][33] and electron transfer reactions. [34][35][36][37][38][39][40][41] Penta-valent uranyl(V) ions are unstable and readily disproportionate to form U(IV) and uranyl(VI) complexes in aqueous solution. Disproportionation reaction of actinyl(V) ions in aqueous solution was computationally studied by Steele et al.…”
Section: Introductionmentioning
confidence: 99%